Anthropology and/as an applied ethics:Theory and methods "hidden" in the Code of Ethics of the American Anthropology Association - Miloš Milenković (University of Belgrade, 2016)
In the context of the forthcoming reactivation of the Serbian Ethnology and Anthropology Association and the normalization of the work of professional associa- tions, as well as their occasional adoption of their ethical codes in Serbia, we are analyzing the Code of ethics of the wolrd’sargest professional anthropological associ- ation – that of American Anthropological Association (AAA). Starting from the as- sumption that ethic codes are not "pure" moral algorithms of what is desirable/correct, but that they are laden by "hidden" theoretical and methodological assumptions, whether by their direct authors, or on the level of the tacit disciplinary knowledge, we are examining what can Serbian ethnological/anthropological community learn out of the genesis, structure, function and critique directed at AAA Code of Ethics. We are also considering the thesis that such codes could be approached as legitimizing narra- tive practices, not unlike those of magic, through which the discipline is attempting to transform itself from the status of fluid and generally socially unrecognized (and even obscure) occupation into a generally recognized, formally licensed and respecta- ble profession. We suggest for anthropology in Serbia to construct its professional sta- tus by forming an alliance with applied ethics offering the services of customization of ethic codes to other professions, through cultural analysis of moral decision-ma- king, instead of legitimizing itself by a contradictory code of ethics, burdened with hollow magic principles and theoretical and methodological issues.